Comparison of the Effectiveness of Suprascapular Nerve Block With Physical Therapy, Placebo, and Intra-Articular Injection in Management of Chronic Shoulder Pain: A Meta-Analysis of Randomized Controlled Trials - Chang, Ke-Vin; Hung, Chen-Yu; Wu, Wei-Ting; Han, Der-Sheng; Yang, Rong-Sen; Lin, Chih-Peng (Archives of physical medicine and rehabilitation, 2016)
To explore the effectiveness of suprascapular nerve block (SSNB) at different timing after administration compared with physical therapy, placebo, and intra-articular injections in patients with chronic shoulder pain. Two electronic data sources, PubMed and Scopus, were mainly searched from the earliest record to September 2015. Eleven randomized controlled trials that compared SSNB with physical therapy, placebo, and intra-articular injections were included, comprising 591 patients. Patient demographics, regimens for SSNB and intra-articular injections, use of fluoroscopy or ultrasound guidance, conjunction with physical therapy, methods of randomization, and measurements of functional change and pain improvement were retrieved. The standardized mean differences (SMDs) of pain relief and functional improvement were calculated 1, 4, and 12 weeks after intervention. Regarding pain relief, SSNB provided better pain relief for 12 weeks compared with physical therapy (SMD=.75; 95% confidence interval [CI], .35–1.14) and placebo injections (SMD=.70; 95% CI, .40–1.00), but was not superior to intra-articular injections. Differences in patient populations and use of pulsed radiofrequency did not cause a significant variation in therapeutic efficacy, but guidance using ultrasound showed consistently better effectiveness than guidance using surface landmarks and fluoroscopy. This meta-analysis demonstrated the superiority of SSNB to placebo and physical therapy and a similar efficacy of SSNB compared with intra-articular injection for treatment of chronic shoulder pain. Ultrasound was the most preferable guidance tool, and future studies are advised to integrate physical therapy in order to improve the long-term effectiveness of SSNB.